Biodegradable artificial reefs enhance food web complexity and biodiversity in an intertidal soft‐sediment ecosystem. Issue 3 (3rd January 2023) - Nauta, Janne; Christianen, Marjolijn J. A.; Temmink, Ralph J. M.; Fivash, Gregory S.; Marin‐Diaz, Beatriz; Reijers, Valérie C.; Didderen, Karin; Penning, Emma; Borst, Annieke C. W.; Heusinkveld, Jannes H. T.; Zwarts, Maarten; Cruijsen, Peter M. J. M.; et al.
Abstract: Reef‐forming species form integral aspects of coastal ecosystems, but are rapidly degrading world‐wide. To mitigate these declines, nature managers increasingly rely on the restoration of habitat‐structuring, reef‐forming species by, for example, introducing artificial reefs that may directly function as complex reef habitat. Since the use of biodegradable structures to restore biogenic reefs is becoming a popular technique, its effectiveness as reef habitat must be assessed. Therefore, we examine the trophic complexity on experimental large‐scale biodegradable artificial reefs using food web network analysis. We placed biodegradable artificial reefs on soft‐sediment intertidal flats in the Dutch Wadden Sea in a large‐scale (~650 m) and 2.5‐year‐long experiment. We compared food web networks and biodiversity indicators between biodegradable reefs and bare controls and quantified species composition inside and near the artificial reef community to assess the expansion of the reef community. During 2.5 years, we observed that artificial reefs changed food web networks compared to bare controls: in species richness (+76%), link density (the number of interactions per species; +15%) and the fraction of basal species (species of lowest trophic level; +40%), but lowered the connectance: the realized fraction of all possible links between species (−33%). Their effects on food web networks increased over time with a higher species richness (+22%) and more complex food web (link density +13%) on the artificial reef 2.5 years after deployment compared to 1.5 years. However, the effects of the reefs did not extend beyond the reef structures; the species composition and biodiversity of macrozoobenthos near the reefs were comparable to the control. Synthesis and applications. This study shows that biodegradable artificial reefs offer an effective tool for the restoration of food web complexity and biodiversity of intertidal soft‐sediment systems. However, application needs to be carefully considered as the reef‐building species did not expand beyond our structures, despite the ambitious spatial extent of this experiment. Therefore, we recommend restoration practitioners to design artificial reefs in such a way that they generate ecosystem connectivity (facilitation of higher trophic levels) and biogeomorphological effects on a landscape scale (reef expansion beyond the structures). Abstract : This study shows that biodegradable artificial reefs offer an effective tool for the restoration of food web complexity and biodiversity of intertidal soft‐sediment systems. However, application needs to be carefully considered as the reef‐building species did not expand beyond our structures, despite the ambitious spatial extent of this experiment. Therefore, we recommend restoration practitioners to design artificial reefs in such a way that they generate ecosystem connectivity (facilitation of higher trophic levels) and biogeomorphological effects on a landscape scale (reef expansion beyond the structures).